The prophetic fount: the ideal of abundance and Milton's recovery of paradise - Barrett, Douglas James (My University, 2000)
The Prophetic Fount reads Milton as one of four great Anglo-American neo-prophetic writers (the others: Blake, Lawrence, Pound) who try to realize an ideal of abundance. An introductory chapter examines abundance as the prophetic ideal, elucidates the neo-prophetics' grounds for commitment to it, and briefly considers neo-prophecy's relation to Hebrew prophecy and Romanticism, seeking in the process to establish Blake, Lawrence and Pound as privileged commentators on Milton. The reading proper divides Milton's poetic career into an early eudaemonism and three great reversals, each initiated by changing needs and strategies regarding abundance. In the Nativity Ode, Milton's First Reversal overthrows the Fifth Elegy's pagan eudaemonism with an antinatural Protestant will to poetic power. After traversing Bloom's revisionary ratios in his early poetry Milton recognizes, however, that poetic divinity is realized not by willful seeking but by generous bestowal, precipitating his expulsion of poetic will in Satan and the dismantling of his romantic world-animation machine. It also generates an attempt to redeem God---by revealing a generosity behind the jealous deity of satisfaction theology---which restructures the Oedipal superego and culminates the Second Reversal with a recovered vision of the Earthly Paradise, Eden. Yet Paradise proves unsustainable. Why? Milton's complex treatment traces the Fall to Eve's narcissistic identification. But Eve's narcissism is itself constructed by the patriarchal voices whose counteridealistic attempts to retain Paradise only exacerbate the constraining abundance that propels Eve and Adam to fall. Anxiety over female sensuous abundance now emerges as underlying patriarchal subordination and compulsive instrumentalism. Recovery requires realization of unmediated abundance: first through moral disengagement from the body ego; second (in Samson Agonistes by catharsis of social (especially female) construction; and finally (in Paradise Regained) by deliberate articulation of an identity as immanent divinity. Milton's Jesus affirms, in contrast even to expansive forms of social constructivism, an identity as abundance, demonstrated by anticipating and rejecting the Hegelian drive for identity through cultural mastery. This proto-mystical asceticism. dissolving performance imperatives. raises possibilities for renewed, if still unrealized, eudaemonism and social engagement.
Thesis (Ph. D.)--University of Washington, 2000
Keywords: Theses--English